Do emotional eating urges regulate affect? Concurrent and prospective associations and implications for risk models of binge eating. Issue 8 (15th January 2014) - Haedt‐Matt, Alissa A.; Keel, Pamela K.; Racine, Sarah E.; Burt, S. Alexandra; Hu, Jean Yueqin; Boker, Steven; Neale, Michael; Klump, Kelly L.
ABSTRACT Objective Emotional eating (EE) reflects an urge to eat in response to emotional rather than physical cues and is a risk factor for the development of binge eating. EE has been conceptualized as an attempt to regulate negative affect (NA), a posited maintenance factor for binge eating. However, no study has examined whether EE urges regulate affect. Further, no studies have examined longitudinal associations between EE urges and positive affect (PA). Method We examined within‐subject longitudinal associations between affect and EE urges in a community‐based sample of female twins (mean age = 17.8 years). Participants (N = 239) completed ratings of affect and EE urges for 45 consecutive days. Results Greater NA was concurrently associated with greater EE urges. Additionally, greater EE urges predicted worse NA for both concurrent and prospective (next‐day) analyses. Finally, lower PA was associated with greater EE urges in concurrent analyses, but there were no prospective associations between changes in PA and EE urges. Discussion EE urges do not appear to effectively regulate affect. EE urges in a community‐based sample appear to have the same functional relationship with affect as binge eating in clinical samples, further supporting EE as a useful dimensional construct for examining processes related to binge eating. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:874–877)